2019
DOI: 10.1029/2018ms001446
|View full text |Cite
|
Sign up to set email alerts
|

Key Elements of Turbulence Closures for Simulating Deep Convection at Kilometer‐Scale Resolution

Abstract: Kilometer‐scale grid spacing is increasingly being used in regional numerical weather prediction and climate simulation. This resolution range is in the terra incognita, where energetic eddies are partially resolved and turbulence parameterization is a challenge. The Smagorinsky and turbulence kinetic energy 1.5‐order models are commonly used at this resolution range, but, as traditional eddy‐diffusivity models, they can only represent forward‐scattering turbulence (downgradient fluxes), whereas the dynamic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…() and Shi et al . () have shown that thermodynamical countergradient areas also exist within convective clouds in simulations at kilometre‐scale resolutions and cannot be represented by traditional eddy‐diffusivity schemes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Shi et al . () have shown that thermodynamical countergradient areas also exist within convective clouds in simulations at kilometre‐scale resolutions and cannot be represented by traditional eddy‐diffusivity schemes.…”
Section: Introductionmentioning
confidence: 99%
“…These areas, referred to as "countergradient areas", are due to nonlocal turbulence effects. Verrelle et al (2017) and Shi et al (2019) have shown that thermodynamical countergradient areas also exist within convective clouds in simulations at kilometre-scale resolutions and cannot be represented by traditional eddy-diffusivity schemes.…”
Section: Introductionmentioning
confidence: 99%
“…The DRM [82] is a more recent LES closure with different design, which has been applied to simulations of clouds in the terra incognita [60,83]. It employs explicit filtering and reconstruction, recognizing the different effects of the explicit LES filter and grid discretization.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…where the tilde denotes the effect of discretization, the overline denotes the explicit filter, and star denotes reconstructed variables. The SGS component still has an eddy-diffusivity based form, but a dynamic eddy diffusivity model [84] is used and an anisotropic version has been developed [83]. One advantage of the dynamic model is that it allows the eddy diffusivity for scalars to be independent of the eddy viscosity.…”
Section: Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation